2017
DOI: 10.1007/s12519-017-0055-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of two novel mutations in the ATP7B gene that cause Wilson’s disease

Abstract: Gene testing is playing an important role in diagnosis of Wilson's disease. The early-onset of Wilson's disease is apparently not associated with P-ATPase domain in the ATP7B protein. Our findings further widen the spectrum of mutations involving the ATP7B gene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Screening patients from the 14 eligible reports [14][15][16][17][18][19][20][21][22][23][24][25][26][27] identified 108 patients with clear WD features. We We observed that the patients with mixed manifestation were significantly older at symptom onset than patients with hepatic symptoms (24.4 V 19.4 years of age, P = 0.039) and patients with neurological symptoms (24.4 V 17.9 years of age, P = 0.015).…”
Section: Characterisation Of Clinical Phenotypementioning
confidence: 99%
“…Screening patients from the 14 eligible reports [14][15][16][17][18][19][20][21][22][23][24][25][26][27] identified 108 patients with clear WD features. We We observed that the patients with mixed manifestation were significantly older at symptom onset than patients with hepatic symptoms (24.4 V 19.4 years of age, P = 0.039) and patients with neurological symptoms (24.4 V 17.9 years of age, P = 0.015).…”
Section: Characterisation Of Clinical Phenotypementioning
confidence: 99%
“…Screening patients from the 14 eligible reports [14][15][16][17][18][19][20][21][22][23][24][25][26][27] identi ed 108 patients with clear WD features. We enrolled 196 patients with WD in the nal analysis, including the current 88 patients with detailed data from southern China.…”
Section: Characterisation Of Clinical Phenotypementioning
confidence: 99%